Oxo/dioxo-vanadium(V) complexes with Schiff base ligands derived from 4-amino-5-mercapto-3-phenyl-1,2,4-triazole - Zabin, Sami Abdullatif; Abdelbaset, Mohamed (European Journal of Chemistry, 2016)
Vanadium complexes containing Schiff base ligands are of great importance and have numerous applications. A series of Schiff base ligands derived from 4-amino-5-mercapto-3-phenyl-1,2,4-triazole and different aldehydes were synthesized and combined with ammonium metavanadate in 2:1 and 1:1 molar ration to yield oxo- and dioxo-vanadium(V) complexes NH4[VO(La-f)2] and NH4[VO2(Lg-h)2], respectively. The structure of the synthesized compounds was confirmed by elemental analysis, UV, IR, NMR, MS and TGA. Complexes with bidentate and tridentate ligands were expected to possess a distorted square-pyramidal structure. The ligands and their complexes have been examined for antimicrobial activity against six types of bacteria and one kind of fungus that widely distributed in Albaha region, Kingdom of Saudi Arabia. The results indicate that some of the complexes were active against C. albicans fungus when used as powder, and no sound activity were shown against any type of tested bacteria.